2022
DOI: 10.5194/essd-14-1183-2022
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral reflectance spectra of floating matters derived from Hyperspectral Imager for the Coastal Ocean (HICO) observations

Abstract: Abstract. Using data collected by the Hyperspectral Imager for the Coastal Ocean (HICO) on the International Space Station between 2010–2014, hyperspectral reflectance spectra of various floating matters in global oceans and lakes are derived for the spectral range of 400–800 nm. Specifically, the entire HICO archive of 9411 scenes is first visually inspected to identify suspicious image slicks. Then, a nearest-neighbor atmospheric correction is used to derive surface reflectance of slick pixels. Finally, a sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Furthermore, our green Noctiluca spectra showed relatively high reflectance in the NIR wavelengths (~706 to ~825 nm) during SGN blooms (Figure 2B and 3A,G). This feature has never previously been reported in studies of green Noctiluca blooms, but has been observed in the reflectance spectra of red Noctiluca (Astoreca et al, 2005;Van Mol et al, 2007;Qi et al, 2019), floating macroalgae (Hu, 2022), and land vegetation (Govender et al, 2007). Reflectances higher than 700 nm are typically low because of high water absorption.…”
Section: Spectral Characteristics Of Green Noctiluca Blooms and Other...mentioning
confidence: 54%
“…Furthermore, our green Noctiluca spectra showed relatively high reflectance in the NIR wavelengths (~706 to ~825 nm) during SGN blooms (Figure 2B and 3A,G). This feature has never previously been reported in studies of green Noctiluca blooms, but has been observed in the reflectance spectra of red Noctiluca (Astoreca et al, 2005;Van Mol et al, 2007;Qi et al, 2019), floating macroalgae (Hu, 2022), and land vegetation (Govender et al, 2007). Reflectances higher than 700 nm are typically low because of high water absorption.…”
Section: Spectral Characteristics Of Green Noctiluca Blooms and Other...mentioning
confidence: 54%
“…Ocean Colour Climate Change Initiative (Valente et al, 2022), National Aeronautics and Space Administration Hyperspectral Imager for the Coastal Ocean reflectance of floating matters (Hu, 2022) or Belgian lakes water quality properties (Castagna et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our high-quality in situ dataset is expected to contribute to algorithm development and potential operational monitoring of similar blooms from current or planned hyperspectral satellite missions such as those of the German Aerospace Center (Environmental Mapping and Analysis Program -EnMAP), the Japan Aerospace Exploration Agency (Hyperspectral Imager Suite -HISUI), the National Aeronautics and Space Administration (Plankton, Aerosol, Cloud, ocean Ecosystem -PACE), or the Italian Space Agency (Hyperspectral Precursor of the Application Mission -PRISMA). The current dataset has a unique geographic location, timescale and satellite overpass match-up window (∼ 2 h) as well as hyperspectral measurements that can be considered an addition to related datasets, such as the updated European Space Agency (ESA) Ocean Colour Climate Change Initiative (Valente et al, 2022) and the National Aeronautics and Space Administration Hyperspectral Imager for the Coastal Ocean reflectance of floating matters (Hu, 2022), or Belgian lake water quality properties (Castagna et al, 2022).…”
Section: Discussionmentioning
confidence: 99%